Implementasi Pendidikan Karakter Dalam Membentuk Sikap Sosial Peserta Didik Melalui Pembelajaran IPS Kelas V SD Negeri 1 Poka: Indonesia - Lilis Subaina; Ode Abdurrachman; Nathalia Y. Johannes (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine how the implementation of character education in shaping the social attitudes of students through social studies learning in class V of SD Negeri 1 Poka. The research method used is qualitative research with a case study approach. the informants used in this study were the head of the school, teachers and fifth grade students of SD Negeri 1 Poka. The data collection techniques used were observation, interviews, questionnaires and documentation. Data analysis techniques used are data reduction, presentation, verification. The results showed that the implementation of character education is very important to build students' social attitudes through social studies learning that integrates social values such as honesty, discipline, responsibility, care and tolerance where students not only understand the learning material but students learn about good social attitudes in everyday life.